2019
DOI: 10.1186/s13229-019-0282-4
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral characteristics of autism spectrum disorder in very preterm birth children

Abstract: Background Lower gestational age may increase autism spectrum disorder (ASD) vulnerability; however, the incidence of ASD diagnosis through a direct assessment on every very preterm birth child on the population base remains unclear. Moreover, the behavioral characteristics of preterm birth ASD are unknown. Methods Every very preterm birth child (gestational age < 32 weeks; birth weight < 1500 g) who was discharged from neonatal intensive care units in Southern Taiwan a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
18
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 48 publications
(53 reference statements)
5
18
2
Order By: Relevance
“…Suspected cases will be referred to pediatric psychologists for further evaluation. In this study, the prevalence of ASD below five years old was 6% (2001–2010), which correlated with other studies [ 30 , 31 ]. Intriguingly, the prevalence of ASD in premature infants after 2010 was decreasing to 0.6%.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Suspected cases will be referred to pediatric psychologists for further evaluation. In this study, the prevalence of ASD below five years old was 6% (2001–2010), which correlated with other studies [ 30 , 31 ]. Intriguingly, the prevalence of ASD in premature infants after 2010 was decreasing to 0.6%.…”
Section: Discussionsupporting
confidence: 92%
“…Impairments in social and communication skills and restricted and repetitive behaviors when it comes to interests and activities are two main characteristics of ASD. The prevalence of ASD in the very preterm population studied in Taiwan correlated to the 7% prevalence rate in a meta-analysis study of children born preterm [ 30 , 31 ]. The high prevalence of ASD in the preterm population might be caused by preterm birth and/or by alteration of immature brain growth, as genetic factors may play a role in both preterm birth and ASD [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is recognised that preterm infants have a 10-fold higher risk of developing autism spectrum disorders. 11,12 It is also hypothesized that a link between maternal/foetal inflammation can lead to deregulation of normal brain development. This pregnancy was also complicated by peri-partum progression of symptoms with cardiac transplant required at 4 months postpartum.…”
Section: Discussionmentioning
confidence: 99%
“…For ASD, a greater proportion of preterm (vs. term-born) males reported comorbidities (sleep apnea, seizure disorders, and ADHD) and people born preterm (particularly females) were more often non-verbal (230). Another recent small study of children with ASD demonstrated that, compared to term children, the preterm children had higher quality peer relationships and socioemotional reciprocity, but poorer non-verbal behaviors that regulate social communication (231). None of the current literature has indicated a problem with diagnosing those born preterm using the current diagnostic criteria.…”
Section: Links Between Eop and Neurodevelopmental Diseasesmentioning
confidence: 99%